(untitled) (Lex localis - Journal of Local Self-Government, 2025)
Purpose: This article provides a comprehensive outlook of Micro, Small and Medium Enterprises Development (MSMED) Act of 2006 in India, understanding its basic structure and principles, subsequent changes in legislation, scope and information on chapters and its relevance at present Approach: The study provides a descriptive approach on MSMED Act 2006, its amendments, and schemes. It forwards information from the statute and public sources to provide an overview of MSMED Act’s structure. Findings: This analysis resurfaces the vision of MSMED Act that it is critical for the growth of MSMEs in India through its Definitions, Chapters, Mechanism & other development initiatives. Economic changes, as reflected in the definitional changes, Non compliance results in penalties and losses of benefits, etc. are analyzed. Research Limitations/Implications: This article is based on review of MSMED Act 2006, a statute and other legislative documents and does not involve primary data. Future exploration in this area might impact further amendments in this statute. Practical Implications: Article will provide a window to understand MSMED Act in a nutshell which is helpful for entrepreneurs, policymakers, and financial institutions to navigate the regulatory law and ensure compliance. Social Implications: MSME promotes the economy in unimaginable ways. MSMED Act contributes in its promotions of economic development, employments, regional upscaling etc,. Effective understanding can promote socio-economic welfare. Originality/Value: This article offers a comprehensive outlook of the MSMED Act of 2006, its evolution, and its continued significance in present competitive glasses.